1998
DOI: 10.1021/np9704922
|View full text |Cite
|
Sign up to set email alerts
|

Petrosaspongiolides M−R:  New Potent and Selective Phospholipase A2 Inhibitors from the New Caledonian Marine Sponge Petrosaspongia nigra

Abstract: Five new bioactive sesterterpenes (1-5) have been isolated from the New Caledonian marine sponge Petrosaspongia nigra Bergquist and named petrosaspongiolides M-R. Their chemical structures were determined from 1D and 2D NMR studies and MS data. All compounds inhibited different preparations of phospholipase A2 (PLA2) by irreversibly blocking these enzymes (particularly human synovial and bee venom, see Table 3), with IC50 values in the micromolar range. Interestingly, these compounds displayed a much lower act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 14 publications
2
76
0
Order By: Relevance
“…Petrosaspongiolide M (25) [25] and cavernosolide (26) [26] are tetracyclic sesterterpenes related to manoalide for which only the relative stereochemistry on the tetracyclic nucleus has been established by NMR data.…”
Section: Absolute Configuration Of Petrosaspongiolide M and Cavernosomentioning
confidence: 99%
See 1 more Smart Citation
“…Petrosaspongiolide M (25) [25] and cavernosolide (26) [26] are tetracyclic sesterterpenes related to manoalide for which only the relative stereochemistry on the tetracyclic nucleus has been established by NMR data.…”
Section: Absolute Configuration Of Petrosaspongiolide M and Cavernosomentioning
confidence: 99%
“…The mixture was poured into H 2 O, extracted with AcOEt, and the crude product was purified by SiO 2 column chromatography (Et 2 O/petroleum ether, 7:3) to give 23 (9 mg) and 24 (2.7 mg). Diacetates 9, 10, 12, 13, 27, 28, 29, 30: The diacetates of cacospongionolide (9, 10), [9] cacospongionolide B (12, 13), [3] petrosaspongiolide M (27, 28), [25] and cavernosolide (29, 30), [26] were prepared as previously described.…”
Section: Monoacetates Of (4s)-manoalide Methyl Analogue 23 and 24mentioning
confidence: 99%
“…In fact, armed with such knowledge, we aim at a rational design of simplified inhibitors of PLA 2 as potential new leads for the treatment of inflammation-related diseases [11][12][13][14][15][16][17][18][19]. In this context, bvPLA 2 represents a very useful model for such studies, as the pharmacological characterization of PM and its derivatives has shown an excellent correlation between inhibitory profiles obtained on this model (group III) enzyme with respect to (group IIa) human secretory counterpart (hsPLA 2 ) [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, Fekih et al 118 reported the semisynthesis of the cheilanthane sesterterpenoid ( ) petro saspongianolide R (199). 119 The synthesis of another tricarbocyclic sesterterpenoid, ( ) nitiol (200) (Fig. 11), 120 a potent enhancer of IL 2 gene expression in human T cell lines, was attempted, and almost achieved, by Dake and co workers.…”
Section: Miscellaneous Tricarbocyclic Sesterterpenoidsmentioning
confidence: 99%